Reduced virulence of Candida albicans PHR1 mutants. - Ghannoum, M A (1995)
Candida albicans mutants lacking PHR1 exhibit a pH-dependent morphogenic defect which is expressed at pH 7.5, a pH comparable to that of mammalian blood (S. M. Saporito-Irwin, C. E. Birse, P. S. Sypherd, and W. A. Fonzi, Mol. Cell. Biol. 15:601-613, 1995). The in vivo relevance of this expression pattern was tested in a mouse model of systemic candidiasis. A phr1/phr1 mutant was found to be less virulent than an isogenic Phr1+ strain and exhibited altered morphological development in vivo. These results indicate that PHR1 contributes to the virulence of C. albicans.